La « frénésie de traduire ». Traduction et politique chez Einaudi - Perle Abbrugiati; Daniela Vitagliano (Laboratoire Italien)
The article analyzes the translation strategy of the Turin publisher Einaudi, from its birth to the sixties. Born under the influence of Luigi Einaudi – the liberal economist who became president of the Italian Republic –, the publishing house will grow into the biggest leftist postwar editor, as Giulio Einaudi will have learned the historical lessons of the Resistance. At all stages of its history, Einaudi as a publishing house was interested in foreign production. Translation strategy appears to be a good indicator of Einaudi’s editorial history and of its role as a cultural operator. We draw the main lines and focus on a few specific cases to show its stakes: translation appears eminently linked to civic engagement.